To Know, To Love and To Heal: PhotoStory and Duo-Ethnography as Approaches to Enhancing Social Justice and Self-Actualization in High School Classrooms - Le, Giang; Blaikie, Fiona; Tran, Vuong (Journal of the Canadian Association for Curriculum Studies, 2020)
This article explores using PhotoStory to promote social justice in the classroom. Interweaving Photovoice (Wang & Burris, 1997) with story-sharing results in PhotoStory, a unique teaching and learning approach that can empower voices of marginalized high school students. Through PhotoStory, we explore possibilities for self-actualization in high schools, where a primary pedagogical goal is to disrupt inequitable social orders and change oppressive behaviors and perceptions. Coming to critical consciousness for both teachers and students is vital, leading to engagement in dialogical pedagogy (Mthethwa-Sommers, 2014). As bell hooks (1994) asserts, oppression emanates in and through differences in relation to sex/gender, class and race. Similarly, Freire (1970) highlights the critical role of literacy skills to equip those who are oppressed to speak truth to power. Contextualized by habitus (Bourdieu, 1986), creators of PhotoStory documentaries come to understand their own and others’ lived experiences, enhancing individual and collective empathy, and promoting healing, offering holistic ways to connect through culturally responsive learning, and flipped and flattened pedagogies. By applying duoethnography (Sawyer & Norris, 2013), three authors, two graduate students and one professor discuss and critique this art-based pedagogical method via experiences of utilizing PhotoStory as an experiential teaching and learning tool. Although the scholars are different in relation to age, status, gender and sexual identities, they are committed to exploring an ethic of care and pedagogical self-actualization that serves our need “to know, to love, and to heal”.